Where do nursing students make mistakes when calculating drug doses? A retrospective study - Laia Wennberg-Capellades; Pilar Fuster-Linares; Encarnación Rodríguez-Higueras; Alberto Gallart Fernández-Puebla; Mireia Llaurado-Serra (BMC Nursing, 2022)
Abstract Background Research internationally shows that nursing students find dosage calculation difficult. Identifying the specific aspects of dose calculation procedures that are most commonly associated with errors would enable teaching to be targeted where it is most needed, thus improving students’ calculation skills. The aim of this study was to analyze where specifically nursing students make mistakes when calculating drug doses. Method Retrospective analysis of written examination papers including dosage calculation exercises from years 1, 2, and 3 of a nursing degree program. Exercises were analyzed for errors in relation to 23 agreed categories reflecting different kinds of calculation or steps in the calculation process. We conducted a descriptive and bivariate analysis of results, examining the relationship between the presence of errors and the proportion of correct and incorrect final answers. Results A total of 285 exam papers including 1034 calculation exercises were reviewed. After excluding those that had been left blank, a total of 863 exercises were analyzed in detail. A correct answer was given in 455 exercises (52.7%), although this varied enormously depending on the type of exercise: 89.2% of basic dose calculations were correct, compared with just 2.9% of those involving consideration of maximum concentration. The most common errors were related to unit conversion, more complex concepts such as maximum concentration and minimum dilution, or failure to contextualize the answer to the clinical case. Other frequent errors involved not extracting the key information from the question, not including the units when giving their answer, and not understanding the question. In general, fewer errors in basic dose calculations were made by students at later stages of the degree program. Conclusions Students struggle with more complex dose calculations. The main errors detected were related to understanding the task and the key concepts involved, as well as not following the correct steps when solving the problem.